Approaches to the Study of Pre-Modern Arabic Anthologies - Cheikh, Nadia Maria El; Orfali, Bilal (Islamic History and Civilization, 2021)
"Literary anthology is a general category of adab that encompasses a range of compilations which has enjoyed tremendous popularity in Arabic literature, probably like no other literature of the world. The aim of this volume is to raise and discuss questions about the different approaches to the study of pre-modern Arabic anthologies from the perspectives of philology, religion, history, geography, and literature. Contributors: Lyall Armstrong, Carl Davila, Matthew L. Keegan, Boutheina Khaldi, Enass Khansa, Jeremy Kurzyniec, David Larsen, Nathaniel A. Miller, Suleiman A. Mourad, Hans-Peter Pökel, Isabel Toral"--